Assessment of the Relationship Between Anthropometric Measurements of Index Finger with Occlusal Vertical Dimension in Dentate Subject - Khalid, Huda; Ahmad, Salman; Rafiq, Fatima; Saeed, Ayesha Mehak; Afzal, Sana; Gohar, Mehtab (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the correlation of anthropometric measurement of length of index finger with occlusal vertical dimension in dentate subjects. Study Design: Analytical cross-sectional study. Place and Duration of Study: Department of Prosthodontics, Foundation University College of Dentistry and Hospital, Islamabad, from Mar to Aug 2024. Methodology: A total of 100 participants (50 males and 50 females) were included using non-probability convenient sampling. All participants exhibited bilateral occlusal stops on natural posterior teeth, as per the selection criteria. Measurements of Occlusal Vertical Dimension (OVD) and Length of Index Finger (LIF) were obtained using Digital Vernier Calliper, with data recorded on a Performa. Results: The study sample included equal number of males and females with an average age of 32.86±8.64 years. The mean OVD of the study population was found to be 68.57±4.89 mm, while the mean LIF was 74.02±6.04 mm. Analysis of finger length measurement revealed a significant correlation with both occlusal vertical dimension and gender (p<0.01). Correlation of LIF with OVD in females (r=0.562, p-value<0.001) suggested a moderate positive correlation, while a weak positive correlation was observed in males (r = 0.302, p-value <0.033). Conclusion: Length of Index Finger shows a moderate correlation with Occlusal Vertical Dimension, particularly in females, and may serve as a simple, non-invasive adjunctive method for Occlusal Vertical Dimension estimation